Bioenergetic adaptations of small intestinal epithelial cells reduce cell differentiation enhancing intestinal permeability in obese mice - Thomas Guerbette; Vincent Ciesielski; Manon Brien; Daniel Catheline; Roselyne Viel; Mégane Bostoën; Jean-Baptiste Perrin; Agnès Burel; Régis Janvier; Vincent Rioux; Annaïg Lan; Gaëlle Boudry (Molecular Metabolism)
Objective: Obesity and overweight are associated with low-grade inflammation induced by adipose tissue expansion and perpetuated by altered intestinal homeostasis, including increased epithelial permeability. Intestinal epithelium functions are supported by intestinal epithelial cells (IEC) mitochondria function. However, diet-induced obesity (DIO) may impair mitochondrial activity of IEC and consequently, intestinal homeostasis. The aim of the project was to determine whether DIO alters the mitochondrial function of IEC, and what are the consequences on intestinal homeostasis. Methods: C57Bl/6J mice were fed a control diet for 22 weeks or a high fat diet (58 kcal% fat). Bioenergetic adaptations of IEC were evaluated on isolated crypts and villi from mouse jejunum. To determine the link between mitochondrial function and alterations of intestinal homeostasis in response to lipid overload, we used the jejunal epithelial cell line IPEC-J2 in vitro and mouse jejunum organoids. Results: Here, we report that DIO in mice induced lipid metabolism adaptations favoring lipid storage in IEC together with reduced number, altered dynamics and diminished oxidative phosphorylation activity of IEC mitochondria. Using the IPEC-J2 cell line, we showed that IEC lipid metabolism and oxidative stress machinery adaptations preceded mitochondrial bioenergetic ones. Moreover, we unraveled the intricate link between IEC energetic status and proliferation / differentiation balance since enhancing mitochondrial function with the AMPK activator AICAR in jejunal organoids reduced proliferation and initiated IEC differentiation and conversely. We confirmed that the reduced IEC mitochondrial function observed in DIO mice was associated with increased proliferation and reduced differentiation, promoting expression of the permissive Cldn2 in the jejunal epithelium of DIO mice. Conclusions: Our study provides new insights into metabolic adaptations of IEC in obesity by revealing that excess lipid intake diminishes mitochondrial number in IEC, reducing IEC differentiation that contribute to increased epithelial permeability.